THE CURRENT STATE AND PROSPECTS OF REGULATION OF DIVORCE PROCEEDINGS: RUSSIAN AND FOREIGN PRACTICE - Yu. V. Zemtsova; Polina P. Nechaeva; Nadezhda N. Shanihina (Russian Studies in Law and Politics)
Background. The divorce process is an important indicator of changes in society, reflecting the main trends in the cultural, legal and economic aspects of the life of the state. The article is aimed at studying the evolution of legal regulation in the USSR and modern Russia. In addition, normative legal acts and statistical data reflecting the main aspects of divorce proceedings in the Russian Federation are studied. The author analyzes some features of the family law of foreign countries in the field of regulation of the divorce process. Based on the conducted research, the authors have developed recommendations aimed at transforming Russian family legislation.